Une restauration « spectaculaire » - Véronique van Caloen; Muriel Verbeeck-Boutin (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article replaces the restoration of a Madonna and Child by Joseph Van der Vecken within the context of a period.Documented by the patron, the intervention did not meet his expectations and resulted in a de-restoration. This fact, far from being anecdotic, is proof of the change in mentalities and sensitivities in the first half of the twentieth century and of the emergence of a new concept of restoration